Securing Health Lessons from Nation-Building Missions - Jones, Seth G. (RAND Corporation, 2006)
RAND researchers analyzed the health components of seven post-World War II nation-building efforts conducted after major conflicts-Germany, Japan, Somalia, Haiti, Kosovo, Afghanistan, Iraq-and found that two factors are correlated with successful health outcomes: planning and coordination, and infrastructure and resources.